Effect of Condensation Heat Transfer Characteristics of Non-condensable Gas in Vertical Rectangular Channel - Huang Jiayu; Tao Leren; Hu Yongpan; Liu Qingqing; Ji Tianwei (Zhileng xuebao)
The current experiment uses de-ionized water as a substance to investigate the influence of a small amount of residual non-condensable gas in a narrow rectangular vertical channel on the condensation heat transfer characteristics. The steam condensation surface heat transfer coefficient is obtained using the thermal resistance separation method, and the influence of non-condensable gas, cooling water mass flow rate, inlet temperature, and effective flux density on the steam condensation surface heat transfer coefficient is analyzed. The main results are as follows. When the heat flux density is 1.668 kW/m2, i.e., the steam mass flow rate is small, a 2% volume of non-condensable gas reduces the condensation surface heat transfer by 33%. However, when the heat flux density is 3.887 kW/m2, i.e., the steam mass flow rate becomes larger, a 2% volume of non-condensable gas only reduces the condensation surface heat transfer by 14%. In addition, the steam condensation surface heat transfer coefficient decreases as the volume percentage of the non-condensable gas increases. It also increases as the cooling water mass flow rate decreases and increases as the inlet temperature and effective flux density increase.